Rh(iii)-catalyzed regioselective intermolecular N-methylene Csp(3)–H bond carbenoid insertion - Xie, Haisheng (Royal Society of Chemistry, 2017)

(untitled) (Chem Sci)
A Rh(iii)-catalyzed regioselective intermolecular carbenoid insertion into the N-methylene Csp(3)–H bond of acyclic aliphatic amides has been achieved, taking advantage of bidentate–chelation assistance. This methodology has been successfully applied to a broad range of linear and branched-chain N-alkylamides, thus providing a practical method for the assembly of diverse beta-amino esters. Mechanism studies and density functional theory (DFT) calculations revealed that a singlet Fischer type carbene insertion via an outer-sphere pathway was involved in this N-methylene Csp(3)–H bond carbenoid insertion.